2020
DOI: 10.1002/hed.26214
|View full text |Cite
|
Sign up to set email alerts
|

Tracheotomy in the SARS‐CoV‐2 pandemic

Abstract: The severe acute respiratory syndrome (SARS)-CoV-2 pandemic continues to produce a large number of patients with chronic respiratory failure and ventilator dependence. As such, surgeons will be called upon to perform tracheotomy for a subset of these chronically intubated patients. As seen during the SARS and the SARS-CoV-2 outbreaks, aerosol-generating procedures (AGP) have been associated with higher rates of infection of medical personnel and potential acceleration of viral dissemination throughout the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 10 publications
0
32
0
4
Order By: Relevance
“…As exposure to aerosol generated by tracheotomy poses healthcare professionals to serious risks of infection [27] , many authors have established recommendations regarding tracheotomy during the COVID-19 pandemic [28 , 29] . In published case series [30] , tracheostomy technique is chosen on the basis of local expertise and resources.…”
Section: Discussionmentioning
confidence: 99%
“…As exposure to aerosol generated by tracheotomy poses healthcare professionals to serious risks of infection [27] , many authors have established recommendations regarding tracheotomy during the COVID-19 pandemic [28 , 29] . In published case series [30] , tracheostomy technique is chosen on the basis of local expertise and resources.…”
Section: Discussionmentioning
confidence: 99%
“…The 2019 novel coronavirus disease (COVID-19) pandemic continues to infect a large number of patients, with fever, dry cough, fatigue, and shortness of breath, acute respiratory distress syndrome (ARDS) as major symptoms. These symptoms are also the risk factors for ventilator dependence [1] . As of October 5, 2020, over 36,600,000 cases and 1,000,000 deaths related to COVID-19 have been reported in at least 200 countries [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Study characteristics are summarized in Table 1. 3,[19][20][21][22] When searching the websites of professional organizations, we found that 3 had produced relevant guidance documents. [13][14][15] Following data extraction and synthesis, the results were categorized according to practice domains for tracheostomy and laryngectomy.…”
Section: Results and Observationsmentioning
confidence: 99%
“…The main recommendations according to each practice area are shown in Table 2. 3,13,14,[19][20][21][22][23][24][25]…”
Section: Results and Observationsmentioning
confidence: 99%